The advanced lung cancer inflammation index as a predictor of kidney stone risk in men: a cross-sectional analysis - Zhou, Yan; Li, Xiaomin; He, Qiying; Feng, Qin; Liu, Yu; Liao, Banghua (Frontiers in Nutrition, 2025)
BackgroundKidney stone incidence and recurrence are increasing, which poses significant health problems. The Advanced Lung Cancer Inflammation Index (ALI) combines body mass index (BMI), albumin, and neutrophil-to-lymphocyte ratio (NLR). It was first created to predict outcomes for cancer patients. Recently, it has been studied as an indicator of overall inflammation and nutrition in other diseases, such as chronic kidney disease, heart failure, acute myocardial infarction, and asthma. This study aimed to evaluate the association between ALI scores and kidney stone risk in adult men, and to assess the potential utility of ALI as an indicative biomarker.MethodsWe analyzed data from 5,429 male participants in the National Health and Nutrition Examination Survey (NHANES, 2007–2018). Weighted logistic regression models were used to examine the relationship between ALI scores and the risk of kidney stones. Non-linear associations were further explored with smoothed curve fitting. The predictive value of ALI was assessed using receiver operating characteristic (ROC) curve analysis. Subgroup analyses were conducted to evaluate the consistency of findings across different demographic and clinical characteristics.ResultsOut of all participants, 572 (10.5%) had a history of kidney stones. For every one-unit increase in ALI score, the risk of having kidney stones decreased by 22.7% (odds ratio = 0.773, 95% CI: 0.675–0.885, P < 0.001). The smooth curve analysis showed a non-linear inverse relationship. The protective effect was stronger when ALI scores were low. Subgroup analyses showed stronger relationships for men aged 60–80, overweight men, former smokers, and men without hypertension, diabetes, or cardiovascular disease. ROC analysis showed ALI had moderate accuracy in predicting kidney stones (AUC = 0.770).ConclusionALI scores were independently linked to a lower risk of kidney stones, especially in men without metabolic diseases. As a simple inflammation and nutrition marker, ALI could help identify people who have a higher risk. However, due to the cross-sectional design of this study, a causal relationship between ALI and kidney stone risk cannot be established. Further prospective studies are needed to validate these findings.